Jaguar at the Edge: movement patterns in human-altered landscapes - Bejarano Alegre, Vanesa [UNESP] (2024)
Human-caused habitat loss and fragmentation have significantly impacted the natural environments of large carnivores, altering their movement patterns and increasing risks such as hunting and road collisions. This study aims to understand the movement of jaguars (Panthera onca) through forests, agriculture of varying patch sizes, their distances to these structures, and roads and drainages. By analyzing movement speed, revisits, time spent inside these structures, and the timing of the last visit, data from 54 GPS-tagged jaguars in South America reveal a pronounced tendency to revisit the edges of these landscape variables. Additionally, jaguars showed a stronger affinity for natural areas, spending more time in large forest patches and reducing their speed in natural drainages. Areas with extensive agriculture had fewer revisits, and jaguars moved faster near roads. These results demonstrate the level of tolerance and the dangers this species faces in a landscape with anthropogenic aspects. This comprehensive assessment of movement patterns and landscape use provides valuable insights into how landscape structure influences habitat preference and mobility rates, which is crucial for future jaguar conservation and management strategies.